Pengaruh Corporate Governance Dan Laba Akuntansi Terhadap Harga Saham - Salamah, Umi; Lindawati, Lindawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to examine the influence of Corporate Governance and Accounting Profit on Stock Prices. The proxies used to measure Corporate Governance are Managerial Ownership and the Board of Commissioners. This type of research is quantitative research. This research uses secondary data in the form of annual reports originating from the Indonesian Stock Exchange (BEI) and company websites. The population in this research is energy sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sampling technique in this research used a purposive sampling method, obtaining 22 companies as research samples. The data analysis technique in this research uses the multiple linear regression analysis method and the data analysis tool in this research uses the Eviews version 12 software program. The results of the research show that together Managerial Ownership, Board of Commissioners and Accounting Profits influence Share Prices. Partially, Managerial Ownership, Board of Commissioners and Accounting Profits influence share prices